Pengembangan Ekonomi Kreatif Desa (Studi Atas Pengembangan Ekowisata Cengklik, Blora) - Muhammad Mustaqim (Jurnal Perspektif, 2018)
The creative economy is a new feature of the informationtechnology era. Ecotourism is one of the developments of thetourism sector that emphasizes conservation and the environment.â€œCengklikâ€ Mountain Ecotourism, in this case, is an effortto develop the villageâ€™s creative economy, which is driven bymillennial generation youth. With a descriptive qualitativeapproach, several strategies for the development of â€œCengklikâ€Mountain ecotourism were obtained, namely by innovating anddeveloping creativity that was able to attract visitors, makemassive promotions, add attractive spots, socialization anddevelopment, reforestation, cooperation with other parties, andprocurement of sanitation facilities and pointing maps.